Efektivitas Bantuan Hukum Advokat di Pos Bantuan Hukum (Posbakum) Pengadilan Negeri Denpasar Kelas I A - Gregorius Yolan setiawan; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
The development of the concept of a rule of law is a product of history, because the formulation or definition of a rule of law is constantly developing in line with the development of human resources. The state is obliged to provide legal assistance with the aim of protecting and prospering the community, this is in accordance with Article 27 paragraph (1) of the 1945 constitution of the Republic of Indonesia, it is stated that all citizens are equal before the law. The purpose of this research is to explain the position of the legal aid post (Posbakum) in the Denpasar District Court Class IA in providing legal assistance to defendants whose sentence is over 5 years and to find out the factors of constraints for the assistance post (Posbakum) in the Denpasar District Court. This research is designed using empirical legal research with a statutory approach, then the data sources used are primary and secondary data. The data collection procedure was carried out by means of interviews and records, which were then analyzed using descriptive qualitative methods. The results showed that the legal assistance provided by lawyers at the legal aid post (Posbakum) at the Denpasar District Court Class IA was effective because it had carried out the provision of law to the underprivileged community either through direct appointment by the judge or through submission of a letter from the poor. according to Law No. 11 of 2011 concerning Legal Aid and in accordance with the MoU which was signed between the Denpasar District Court Class 1 A and the legal aid post. As for the factors that were often faced by the aid post (Posbakum), namely the defendant himself, namely that the family of the defendant was difficult to find to ask for a statement of incapacity and the community's low knowledge of legal aid facilities.